"Their God is their belly": Moravian missionaries at the Weipa Mission (1898–1932), Cape York Peninsula. Issue 2 (12th June 2015) - Morrison, Michael; McNaughton, Darlene; Keating, Claire
Abstract: The Weipa Mission (1898–1932) on Cape York Peninsula (north‐eastern Australia) was one of seven Australian missions designed and staffed by the Moravian Church during the nineteenth and early twentieth centuries. We present findings of archaeological and historical research that illustrate key aspects of the settlement's development and operations. Moravian missionaries at Weipa aimed to create a built landscape that reshaped Aboriginal social, cultural and economic relations, with particular emphasis on children through the use of a dormitory system. However, their efforts were mediated by the open spatial and social boundaries of the settlement, which enabled Aboriginal people to make choices about the nature and extent to which they engaged with the mission. Adopting a political economy approach, we show that this openness emerged through complex social relationships between missionaries and Aboriginal people. While missionaries required access to children and adults, they lacked the ability (or will) to maintain a resident population through force, with limited financial resources also hampering their activities. Instead, Aboriginal people came and went from the settlement, with some establishing and maintaining social relationships with missionaries to access economic and social benefits. We argue that these social relationships led to the development of the settlement as a more open domain.